(untitled) (Fiep Bulletin - online, 2015)
This study aims at discussing the power relationships that permeate the capoeira game and consolidate in the master’s mythical figure. We acknowledge the existence of a symbolic universe underlying the capoeira game, whose meanings may be unveiled through a study of the myth and its narratives, in an attempt to understand, or decipher, some peculiarities connected to the modality being considered. The dialogue between myth and capoeira was built according to the anthropologist Pierre Ansart’s theoretical perspective, revealing the extent to which the mythical narratives are organized, contributing to the preservation of the social relationships inside the groups. The myth may hierarchize and suggest values, orienting both the actions and practices of the social groups, getting incorporated in the capoeira songs and legitimating the master’s discourse.